Kajian Prosedur Penentuan Harga Kelarutan dan Tetapan Hasil Kali Kelarutan (Ksp) sebagai Bahan Materi Praktikum Kimia Dasar - Ade Trisnawati (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2024)
This research aims to provide an overview of experimental procedures to determine the correct price and solubility product (Ksp) as materials in introductory chemistry practical work. This research was preceded by an experiment to assess solubility values ​​and products, and then a descriptive analysis was carried out regarding the results obtained. Based on the results of the study, it is known that the steps for determining Ksp are (1) Calculating the mass of substances that can dissolve in a specific volume of solvent, (2) Calculating the mass of substances that can dissolve in 1 liter of solvent (solubility in g/L), (3) Calculating moles substances that can dissolve in 1 liter of solvent (molar solubility in units of mol/L), (4) Calculate the concentration of each ion, and (5) Calculate the Ksp of the compound from the concentration of each ion raised to the power of the reaction coefficient.